2003
DOI: 10.1038/sj.hdy.6800353
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetic tests of recent senescence theory: age-specific mortality and male fertility in Drosophila melanogaster

Abstract: Quantitative genetic models of aging predict that additive genetic variance for fitness components should increase with age. However, recent studies have found that at very late ages, the genetic variance components decline. This decline may be due to an age-related drop in reproductive effort. If genetic variance in reproductive effort affects the genetic variance in mortality, the decline in reproductive effort at late ages should lead to a decrease in the genetic variance in mortality. To test this, we carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 49 publications
9
63
2
1
Order By: Relevance
“…The idea of antagonistic pleiotropy was originally developed in the context of senescence [67], and states that alleles that increase fitness at early stages but have deleterious effects late in life will tend to accumulate in the population because selection does not operate as efficiently later on in life. Antagonistic pleiotropy has some empirical support in the context of senescence [68,69], and its role in senescence has in fact recently been investigated in a hermaphroditic species [70]. It seems reasonable that sexual antagonism via antagonistic pleiotropy could operate in sequential hermaphrodites, where alleles that increase fitness in the first sex at the expense of the second sex should spread owing to a decreased efficiency of selection at later stages in life.…”
Section: Sexual Antagonism In Sequential Hermaphroditesmentioning
confidence: 99%
“…The idea of antagonistic pleiotropy was originally developed in the context of senescence [67], and states that alleles that increase fitness at early stages but have deleterious effects late in life will tend to accumulate in the population because selection does not operate as efficiently later on in life. Antagonistic pleiotropy has some empirical support in the context of senescence [68,69], and its role in senescence has in fact recently been investigated in a hermaphroditic species [70]. It seems reasonable that sexual antagonism via antagonistic pleiotropy could operate in sequential hermaphrodites, where alleles that increase fitness in the first sex at the expense of the second sex should spread owing to a decreased efficiency of selection at later stages in life.…”
Section: Sexual Antagonism In Sequential Hermaphroditesmentioning
confidence: 99%
“…Since then additional direct and indirect evidence for the deleterious effects of inbreeding on adult survival has been provided by a number of studies on species such as D. melanogaster and D. simulans (e.g. Hughes 1995a; Snoke and Promislow 2003;Vermeulen and Bijlsma 2004;Swindell and Bouzat 2006a;Vermeulen et al 2008;Wright et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Most tests of mutation accumulation models with Drosophila have found that the genetic load and/or genetic variance for fitness traits increase with age (Snoke and Promislow, 2003;Gong et al, 2006;Swindell and Bouzat, 2006;Borash et al, 2007), although results have varied among lines and/or differed between the sexes (Lesser et al, 2006;Reynolds et al, 2007). The evidence is more equivocal in non-Drosophila systems (Wilson et al, 2008).…”
Section: Discussionmentioning
confidence: 87%
“…For example, as beetles age, the mortality rate decelerates (Fox and Moya-Larañ o, 2003), approaching a mortality plateau that is the same for inbred and outbred beetles (that is, the u(t) curves converge), and the estimated inbreeding load converges on 0. The presence of mortality plateaus, or the age at which populations reach their plateau, may reflect adaptation to the laboratory (Promislow and Tatar, 1998;Snoke and Promislow, 2003;Rauser et al, 2006). However, mortality plateaus have been observed in a variety of experiments with seed beetles, including populations recently collected from the field and not adapted to the laboratory culture (Tatar et al, 1993;Tatar and Carey, 1995;Fox et al, 2003b;Fox and Moya-Larañ o, 2003), that also provide no evidence for an increase in the inbreeding load with age (Fox et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation